The effect of flip chart media on young women's knowledge of personal hygiene during menstruation at SMP O Mangunharjo, Musi Rawas Regency - Desi Fitriani; Sanisahhuri Sanisahhuri; Beti Susanti (Alma Ata University Press, 2022)
Background: Personal Hygiene during menstruation is a component of personal hygiene that plays an important role in the status of a person's health behavior. The impact of personal hygiene problems if not maintained will cause excessive microorganisms such as fungi, bacteria, viruses that interfere with the function of reproductive organs and the occurrence of infection.Objectives: This study aims to determine the effect of Flip Chart media on the knowledge of adolescent girls about Personal Hygiene During Menstruation at SMP O Mangunharjo, Musi Rawas Regency.Methods: This study uses a quasi-experimental design using a one group pre-post test. This research was conducted at SMP O Mangunharjo, Musi Rawas Regency, with a population of 90 grade 7 adolescent girls. The sample of this research is 47 people using purposive sampling technique. Bivariate analysis was conducted to determine the effect of Flip Chart media on young women's knowledge of Personal Hygiene During Menstruation at SMP O Mangunharjo, Musi Rawas Regency with the Wilcoxon Signed Ranks Test.Results: The results showed the average knowledge before counseling using Flip Chart media was 6.36, after counseling using Flip Chart media was 8.70. The results of the Wilcoxon Signed Ranks test obtained p-value = 0.000 <0.05, there was an influence of Flip Chart media on the knowledge of young women about Personal Hygiene During Menstruation at SMP O Mangunharjo, Musi Rawas Regency.Conclusions: There is a difference in knowledge before and after counseling using Flip Chart media, then Ho is rejected and Ha is accepted. So there is an influence of the Flip Chart media on the knowledge of young women about Personal Hygiene During Menstruation at SMP O Mangunharjo, Musi Rawas Regency.